Design of mobile robot for gas and temperature detection inside tanks based on internet of things - Kusuma W, Toni; Syuja, M.; Sinaga, Guido; Saputra, Rizki (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
Monitoring gas level and temperature in the fuel storage tank area uses DHT-11 and MQ-07 sensors. This sensor will send the readings obtained to the system, so that supervisors can find out each gas PPM level due to unknown leaks without having to witness the location of the tank. Normal PPM is 0-15 PPM and if it exceeds it, it needs to be checked directly. For certainly in checking, the test can be carried out 5 times at varying distances or around the steam. Continuous control of the distance of the object monitored by the sensor greatly influences the quality of the readings. The data transmissions medium used in this system is webapps, using a internet network connected to the control system. The ESP32 cam camera will capture video and transmit it to a web server, as well as gas and temperature sensors